Effect of Ultra-High-Pressure Treatment on Gastrodia elata Blume: Drying Characteristics, Components, and Neuroprotective Activity - Hongjing Dong; Shuang Liu; Xinming Wang; Meng Li; Buddhika Niroshie Perumpuli Arachchige; Xiao Wang (Foods)
Gastrodiae Rhizoma (GE), a popular food in China, is stored and consumed after steaming, which can lead to the degradation of active substances and a decrease in its quality. Therefore, this study explored the potential application of ultra-high-pressure (UHP)-assisted hot air drying in improving the quality of GE. The results indicated that UHP pre-treatment could preserve the original cross-sectional color of GE and increase the degrees of freedom of water in GE samples. Compared with traditional steaming pre-treatment (18 h), UHP pre-treatment at 500 MPa significantly shorted the time (10 h) required for the GE samples to reach drying equilibrium. Meanwhile, the UHP-assisted hot air drying method (60 °C) could reduce the activity of β-D-glucosidase and avoid the degradation of active substances. Finally, UHP pre-treatment improved the neuroprotective activity in vivo. Overall, UHP-assisted hot air drying could improve the quality of GE samples. This study provides a simple method for improving the quality of GE samples and offers a reference for subsequent research on the influence of UHP on GE.